Comparative analysis of the investigation paper in healthcare between Malaysia and Australia / Jasni Turiman and Haznita Zainal Abidin - Turiman, Jasni; Zainal Abidin, Haznita (2014)
An investigation paper does provide benefit to all enforcement officer, whether they are from the Private Healthcare Facilities and Services or the principle enforcement police officer. The research identified the problem statements and objectives of the study. Currently there is no proper standard while preparing the investigation paper in Private Healthcare Facilities and Services unit and this could lead to the case ended up being challenge in court. This study examines the laws, regulation and procedures in Malaysia relating to criminal activities and comparing the law between Malaysia and Australia . The research referred to several case studies. Data was taken from two cases and supporting materials such as books, journals, articles from the internet sources, lecture notes and seminars. The issues and challenges of investigation paper are elaborated. The argument of a case is by a series of case discussions. Human factors have been identified as an important contributing factor in producing good investigation paper. Comparable police investigation and Private Healthcare Facilities and Services investigation paper are also described. A good investigation paper has a direct effect on the outcome of the cases brought to court for prosecution. Finally, there is a gap of knowledge among enforcement officers thus policy changers need to urgently enhance the standard of in preparing better investigation papers.